Promoting Concordance in Mental Health - McNay,Lisa (...ed); Snowden,Austyn(...ed) (London Quay Books, 2012)
presents a practical, skilled approach to concordance. It explores the concept of concordance and compliance and addresses specific challenges faced by health professionals, providing clear methods for overcoming them.
Includes bibliographical references and Index
Keywords: Mental health promotion-Concordances; Mental Health-Concordances; Psychiatric-Health-Concordances